Effect of inspiratory pressure support on exercise tolerance and breathlessness in patients with severe stable chronic obstructive pulmonary disease. Issue 10 (October 1994) - Keilty, S E; Ponte, J; Fleming, T A; Moxham, J
Abstract : BACKGROUND--In patients with chronic obstructive pulmonary disease exercise tolerance is commonly limited by breathlessness. These patients have an increased ventilatory load at rest which is exacerbated during exercise. The purpose of this study was to investigate the effect of supporting ventilation by non-invasive inspiratory pressure support (IPS) during submaximal treadmill exercise in such patients to see if they would experience less breathlessness and improve their exercise capacity. METHODS--Eight men with disabling breathlessness due to chronic obstructive pulmonary disease (COPD) (mean (SD) FEV1 0.73 (0.2) 1) were studied. Patients walked on a treadmill until their sensation of breathlessness, scored at one minute intervals, reached level 5 ("severe") on the 10-point Borg scale. Studies were performed with IPS (mean airway pressure 12-15 cm H2O), continuous positive airway pressure (CPAP 6 cm H2O), and with oxygen (2 l/min via a mask) in random order on three separate days. Each of these walks was compared with a control walk using a sham circuit (breathing air via an oxygen mask at 2 l/min from an unlabelled cylinder), and with a baseline walk in which patients walked freely on the treadmill. On cessation of exercise, distance achieved and a leg fatigue score were recorded. RESULTS--No patients stopped due to leg fatigue, all stopping only when their sensation of breathlessness had reached level 5 on the Borg scale. IPS improved median walking distance by 62% compared with the control walk (sham circuit). There was no change in walking distance with either CPAP or oxygen at 2 l/min. There was no difference between the control and the baseline walks. CONCLUSIONS--Inspiratory pressure support can reduce breathlessness and increase exercise tolerance to submaximal treadmill exercise in patients with COPD. This could have implications for the rehabilitation of these severely disabled patients.